POLITYCZNY MECHANIZM PODZIAŁU DOCHODU W SPOŁECZEŃSTWIE - Walasik, Artur (Wydział Prawa i Administracji UAM, 1998)
The article attempts to determine the factors and the intensity of their impact on the distribution o f income among particular members of a society. A classifications o f the distribution norms when based on generic criterion makes it possible to define two fundamental mechanisms o f such a distribution: the on natural, and the other — social. The author discusses shortly some other kinds of a distribution such as economical mechanism and the axiological one, Nevertheless he concentrates principally on political mechanism the norms of which remain within the framework of activities of public authorities. The may have recourse to the instruments of distribution of charging nature (taxes) and, also, of discretional nature (structure of public expenses) — both with the aim of diminishing a disproportion in incomes realized by particular social groups and, as well, with the aim of enforcing some particular interests by using such instruments. A full representation of activities of public authorities in the domair o f distribution cannot, however, restrain itself to an analysis of the subjects charged with taxes but it should be completed with analysis of most important parameters related to the directions of the distribution of public income and, as well, of parameters that confirm the existence of undeiprivilegedness (or: overprivilegedness) in particular groups of a society in relation with the issue of public consommation.
POLITICAL MECHANISM OF INCOME DISTRIBUTION IN A SOCIETY